PEMBUATAN DAN PENGGUNAAN ALAT KONVERTER UNIVERSAL OSILOSKOP SEBAGAI PERALATAN KATAGORI 2 PADA PRAKTIKUM ELEKTRONIKA DAYA - Lastera, I Wayan; Arsikaputra, I Putu (Jurnal SPEKTRUM, 2020)
To display electric waveforms in power electronics practicum, the instrument used is an oscilloscope. With the limited range of test voltages from oscilloscopes the measurement results for the power electronics lab are not good enough. To improve the results of practicum, one effort that can be done is by making an universal converter oscilloscope tool. The potential of this universal converter tool can be identified by using it in uncontrolled AC electricity testing, controlled AC electricity testing, uncontrolled DC electricity testing and controlled DC electricity testing. The test data obtained are tabulated and analyzed descriptively, in order to be able to see and be able to infer the potential of the oscilloscope universal converter. The test results show that the use of an oscilloscope universal converter able to improve the measurement results for power electronics practicum, proven to be able to be used in AC and DC mains voltage either uncontrolled or controlled with normal waveform display, so that it can be used as category 2 equipment in the power electronics practicum, in order to add equipment to the laboratory.